SLC6A4 Repeat and Single-Nucleotide Polymorphisms Are Associated With Depression and Rest Tremor in Parkinson's Disease: An Exploratory Study - Wang, Jian-Yong; Fan, Qian-Ya; He, Jia-Hui; Zhu, Shi-Guo; Huang, Chen-Ping; Zhang, Xiong; Zhu, Jian-Hong (Frontiers in Neurology, 2019)
Introduction: Level of serotonin is mainly regulated by the serotonin reuptake transporter encoded by SLC6A4. The promoter region of SLC6A4 bears a repeat polymorphism 5-HTTLPR and a single nucleotide polymorphism rs25531. We have previously studied the association between these two variants and sporadic PD. The objective of the current study was to determine whether the SLC6A4 polymorphisms were associated with key motor and non-motor symptoms of PD. Methods: A total of 370 PD patients of Han Chinese were included. Associations between the SLC6A4 polymorphisms and PD symptoms including depression, intellectual impairment, tremor and rigidity were analyzed. Results: 5-HTTLPR was associated with depression in PD patients and presence of the LL genotype was protective against the depression risk. The rs25531 was associated with rest tremor in PD and the A allele serves as a recessive risk allele. No associations were found in the two polymorphisms with respect to intellectual impairment and rigidity in the cohort. Conclusion: The current study reveals two PD symptoms associated with SLC6A4 polymorphisms, and provides new insight into how serotonergic system genetically participates in the symptomatic progression of PD. Further study is warranted in additional populations.